The complete mitochondrial genome of Lumbricus rubellus (Oligochaeta, Lumbricidae) and its phylogenetic analysis - Zhang, Qingzheng (Mitochondrial DNA B Resour, 2019)
The complete mitochondrial genome of Lumbricus rubellus was analyzed by next-generation sequencing. The mitogenome was 15,464 bp in length, comprising 13 protein-coding genes (PCGs), 22 transfer RNAs, 2 ribosomal RNAs, and a non-coding region. The phylogenetic analysis of 13 PCGs within the class Oligochaeta suggested that L. rubellus was placed as sister to L. terrestris of the same genus. The results obtained here can contribute to the phylogenetic analysis of earthworms.